Increased Postural Demand Is Associated With Greater Cognitive Workload in Healthy Young Adults: A Pupillometry Study - Kahya, Melike; Wood, Tyler A.; Sosnoff, Jacob J.; Devos, Hannes (Frontiers in Human Neuroscience, 2018)
Introduction: Balance tasks require cognitive resources to ensure postural stability. Pupillometry has been used to quantify cognitive workload of various cognitive tasks, but has not been studied in postural control. The current investigation utilized pupillometry to quantify the cognitive workload of postural control in healthy young adults. We hypothesized that cognitive workload, indexed by pupil size, will increase with challenging postural control conditions including visual occlusion and cognitive dual tasking. Methods: Twenty-one young healthy adults [mean ± standard error of the mean], [age = 23.2 ± 0.49 years; 12 females] were recruited for this study. Participants completed four tasks: (1) standing with eyes open; (2) standing with eyes occluded (3) standing with eyes open while performing an auditory Stroop task; and (4) standing with eyes occluded while performing an auditory Stroop task. Participants wore eye tracking glasses while standing on a force platform. The eye tracking glasses recorded changes in pupil size that in turn were converted into the Index of Cognitive Activity [ICA]. ICA values were averaged for each eye and condition. A two-way Analysis of Variance with post-hoc Sidak correction for pairwise comparisons was run to examine the effect of visual occlusion and dual tasking on ICA values as well on Center of Pressure [CoP] sway velocity in anterior-posterior [AP] and medio-lateral [ML] directions. A Pearson’s correlation coefficient was utilized to determine the relationship between ICA values and CoP sway velocity. Results: Significant within-condition effect was observed with visual occlusion for the right eye ICA values [p = 0.008]. Right eye ICA increased from eyes open to eyes occluded conditions [p = 0.008]. In addition, a significant inverse correlation was observed between right eye ICA values and CoP sway velocity in the ML direction across all the conditions [r = -0.25, p = 0.02]. Conclusion: This study demonstrated support for increased cognitive workload, measured by pupillometry, as a result of changes in postural control in healthy young adults. Further research is warranted to investigate the clinical application of pupillometry in balance assessment.